2007
DOI: 10.1016/j.ecosys.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A survey of enterprise reforms in China: The way forward

Abstract: The strategic importance of the state owned enterprise (SOE) sector to the Chinese economy cannot be underestimated, thus the success of SOE reform is a significant factor in China's future economic prosperity. The dilemma facing state authorities is to develop market-orientated corporations while at the same time coping with potentially high unemployment and a range of equity and social justice issues. This paper presents an analysis of the current issues in SOE reform in China, drawing on relevant empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 63 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…In China, all SOEs that go public are partially privatised so that the state maintains control. The state still owns the majority of outstanding shares of SOEs after IPOs (Hovey and Naughton, 2007). Those facts suggest that all SOEs are politically connected.…”
Section: Univariate Analysesmentioning
confidence: 96%
“…In China, all SOEs that go public are partially privatised so that the state maintains control. The state still owns the majority of outstanding shares of SOEs after IPOs (Hovey and Naughton, 2007). Those facts suggest that all SOEs are politically connected.…”
Section: Univariate Analysesmentioning
confidence: 96%
“…In fact, being state owned decreases firms’ chances of becoming exporters. It has been widely reported that China's SOEs are less efficient and less productive, but at the same time, they might have access to some local advantages such as easy bank loans from the state‐owned banks (Hovey and Naughton, ). Such institutional advantages and policy support might help SOEs overcome some of the market entry costs, if not productivity per se .…”
Section: Some Sensitivity Analysesmentioning
confidence: 99%
“…Mainland Chinese firms are able to issue two types of stock, namely A-shares and B-shares, Therefore, with the decreased necessity of market segmentation, it is doubtful whether there is a reason for the B-share market to continue to exist (Hovey and Naughton, 2007).…”
Section: Market Structure Of Mainland Chinese Exchangesmentioning
confidence: 99%